Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/psyp.13394
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal neural responses to harmonic syntactic structures in congenital amusia

Abstract: In music, harmonic syntactic structures are organized hierarchically through local and long-distance dependencies. This study investigated whether congenital amusia, a neurodevelopmental disorder of pitch perception, is associated with impaired processing of harmonic syntactic structures. For stimuli, we used harmonic sequences containing two phrases, where the first phrase ended with a half cadence and the second with an authentic cadence. In Experiment 1, we manipulated the ending chord of the authentic cade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 65 publications
1
16
0
1
Order By: Relevance
“…LPC is an ERP correlate of syntactic processing in language (Friederici et al, 1993;Kaan et al, 2000;Hahne, 2001;Mueller et al, 2005;Phillips et al, 2005) and music (Patel, 1998;Neuhaus, 2013;Sun et al, 2018), reflecting the integrative process and the cognitive resources allocation. Evidence of LPCs for the processing of non-adjacent tonal integration is also given by previous research on musical syntax violation (Koelsch et al, 2013;Ma et al, 2018a,b;Zhou et al, 2019). The LPC effect observed in our study may be ascribed to the more cognitive resources required by combining local information into higher global hierarchical units for the nested structure than the non-nested structure.…”
Section: The Discrepancy Between Cognitive and Emotional Responses Tosupporting
confidence: 87%
See 2 more Smart Citations
“…LPC is an ERP correlate of syntactic processing in language (Friederici et al, 1993;Kaan et al, 2000;Hahne, 2001;Mueller et al, 2005;Phillips et al, 2005) and music (Patel, 1998;Neuhaus, 2013;Sun et al, 2018), reflecting the integrative process and the cognitive resources allocation. Evidence of LPCs for the processing of non-adjacent tonal integration is also given by previous research on musical syntax violation (Koelsch et al, 2013;Ma et al, 2018a,b;Zhou et al, 2019). The LPC effect observed in our study may be ascribed to the more cognitive resources required by combining local information into higher global hierarchical units for the nested structure than the non-nested structure.…”
Section: The Discrepancy Between Cognitive and Emotional Responses Tosupporting
confidence: 87%
“…Until recently, Koelsch et al ( 2013 ) first explored the neural responses to the processing of nested structure and found that structurally irregular endings elicited larger early right anterior negativity (ERAN) and N5 components than structurally regular endings, reflecting the structural integration for long-distance dependence. Similar components, such as N5 and late positive component (LPC), were also observed in music nested structure processing by Chinese listeners (Ma et al, 2018a , b ; Zhou et al, 2019 ). These results demonstrated the integration of harmonic cadence into the originally tonal context and the cognitive processing of nested structure.…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…It is well known that Western tonal music has been widely spread in many areas of the world. Due to familiarity with tonal conventions of Western music, both Western 76 , 77 and Chinese listeners 78 , 79 can process Western tonal structures and exhibit similar neural responses to these tonal structures. Therefore, our findings could be applicable to many other populations who speak alphabetic languages.…”
Section: Discussionmentioning
confidence: 99%
“…音乐是情绪的语言。在日常生活中, 人们常 常通过音乐调节情绪、舒解压力并在音乐中得到 享受 (Juslin & Sloboda, 2010)。在音乐聆听中, 人 们不仅能知觉和体验音乐所传递的微妙的情绪变 化 (Shen et al, 2018;Zentner et al, 2008), 还会激 活与加 工一 般 情绪事 件相 似 的脑区 与神 经 环路 (Koelsch, 2018) 也 被 称 之 为 " 悬 念 感 " (Granot & Eitan, 2011; 收稿日期: 2020-04-03 * 国家自然科学基金(31470985, 31971034)与中国博士 后科学基金(Y9BH032001)资助。 通信作者: 杨玉芳, E-mail: yangyf@psych.ac.cn Lehne & Koelsch, 2015b) (Berry, 1976;Hindemith, 1937), 同时也是引发音乐内在意义的 前提 (蒋存梅, 2016) (Hutchinson & Knopoff, 1978)。不协和和弦的振动频率会干扰内耳基底膜 的听觉接收器 (Helmholtz, 1913)。对于展开的音乐 Bigand et al, 2014;Collins et al, 2014;Leman, 2000)Bigand et al, 1996;Farbood, 2012;Krumhansl, 1996) 、 速 度 (Farbood, 2012;Ilie & Thompson, 2006;Madsen et al, 1997)等其他声学 (Bigand & Parncutt, 1999;Bigand et al, 1996)、单声部旋律 (Farbood, 2012;Wong et al, 2009), 还 能 够 加 工 真 实 音 乐 片 段 中 的 紧 张 感 (Lehne et al, 2013;Lehne et al, 2014 (Jiang et al, 2019;Zhou et al, 2017), 而且 也无法加工调性结构规则 (Jiang et al, 2016;Zhou et al, 2019) (Lerdahl & Jackendoff, 1983;Rohrmeier, 2011)。和 声结构与节拍结构的加工是音乐认知的两个重要 方面 (Fitch, 2013;Koelsch, 2013;Sun et al, 2018;Sun et al, 2020), 也是诱发音乐情绪体验的重要 线索 (Koelsch, 2014;Witek et al, 2014)…”
Section: 引言 unclassified